Training in cultural heritage preservation: the experience of heritage institutions in Nigeria (2013)
The preservation of cultural heritage materials is one of the daunting tasks of heritage institutions in Nigeria. The task becomes more daunting against the background of the various challenges facing heritage institutions in the country. Among these critical challenges is the shortage of human resources required to undertake the task of heritage preservation. In the early days of their existence, heritage institutions in Nigeria relied heavily on foreign institutions and international organizations for the education and training of heritage personnel. For instance, the School of Archival Studies of the National Archives of India, New Delhi served as a training centre in preservation and restoration of archival materials for staff of the National Archives of Nigeria. In addition, the regional centres established in Accra, Ghana and Dakar, Senegal with the assistance of UNESCO also met the training needs of archives personnel from English-speaking and French speaking countries in archival work. Similarly UNESCO assisted in establishing the museum training centre at Jos, Plateau State, Nigeria in 1963. The centre was later upgraded to the Institution of Archaeology and Museum Studies to provide management trainee programmes in various aspects of heritage preservation. In the library sector, heavy reliance was placed on the preservation component of the curricula of the various library schools within and outside the country where library personnel had their professional training in librarianship. The down-turn in the nation's economy in the 1980s affected every aspect of life including capacity building in heritage preservation. What then is the coping strategy and how are the heritage institutions in Nigeria, particularly libraries and archives, meeting their staff training needs in heritage preservation? This is the focus of this paper. The specific objectives are to investigate the training needs of workers in heritage institution in Nigeria, the training programme available, aspects of heritage preservation covered the facilities in place and the obstacles encountered. Data were collected from librarians and archivists in selected Nigerian libraries and archives using participatory focus group discussion method. Based on the findings, recommendations were be made towards improving the process of human resources development in cultural heritage preservation in Nigeria.